2023
DOI: 10.4244/aij-d-22-00040
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous left atrial appendage closure: beyond the classic indications

Abstract: Percutaneous left atrial appendage closure (LAAC) has proven to be an effective alternative to oral anticoagulation (OAC) for stroke prevention in patients with non-valvular atrial fibrillation (NVAF). International guidelines traditionally recommend LAAC for NVAF patients at high thromboembolic risk and contraindication to or at high risk for OAC. However, there are many other clinical situations in which this procedure may also be beneficial. This paper discusses the potential role of LAAC in specific haemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In this issue of EuroIntervention, Guérios et al review potential candidates for LAAC who are not classically indicated 12 . This review expands our knowledge about the types of disease conditions that should be considered a contraindication for long-term anticoagulation.…”
mentioning
confidence: 99%
“…In this issue of EuroIntervention, Guérios et al review potential candidates for LAAC who are not classically indicated 12 . This review expands our knowledge about the types of disease conditions that should be considered a contraindication for long-term anticoagulation.…”
mentioning
confidence: 99%